Pt-doped armchair graphene nanoribbon as a promising gas sensor for CO and CO2: DFT study - Ehab Salih (17075206) (2021)
In this work, four armchair graphene nanoribbon (AGNR) based sensor materials were built using Atomistic ToolKit Virtual NanoLab (ATK-VNL) and utilized to detect carbon monoxide (CO) and carbon dioxide (CO2) gases. First, the effect of passivating AGNR on the sensing performance toward CO and CO2 gases has been investigated, where AGNR was passivated with hydrogen (H-AGNR) and nitrogen (N-AGNR). The obtained results reflected no significant changes in the adsorption parameters of CO and CO2 molecules on H-AGNR and NAGNR. Particularly, the adsorption energies between H-AGNR and N-AGNR systems and CO were found to be − 0.446 and − 0.436 eV, while for the case of CO2, the adsorption energies were found to be − 0.426 and − 0.432 eV, respectively. To enhance the sensing performance, both H-AGNR and N-AGNR systems were doped with platinum (Pt) forming another two systems: Pt–H-AGNR, and Pt–N-AGNR. After doping, the results revealed a significant increase in the adsorption energy to almost 9 times than the non-doped systems for the cases of CO on Pt–N-AGNR as well as CO2 on both Pt–H-AGNR and Pt–N-AGNR. Moreover, an increase of almost 13 times was observed in the adsorption energy for the case of CO on Pt–H-AGNR. Besides to the adsorption energy (Eads), the adsorption distance ((D), charge transfer (ΔQ), the density of states (DOS), as well as the band structure have been examined to confirm the adsorption of CO and CO2 on the four systems. Other Information Published in: Physica E: Low-dimensional Systems and Nanostructures License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.physe.2020.114418